Rol de las ecotecnologías, tecnologías limpias y de tratamiento, en el control de la contaminación generada por las curtiembres de Trujillo - Perú - Silva Villanueva, José Luis (2011)
The present research work's fundamental objective was to evaluate and comparing ecotecnnologies's role: Clean and treatment's technologies in the control of the contamination generated for them Trujillo's tannery, contamination than no only he goes against the health and the enviromental; rather product lost that efficiency proves to be falling represents that industrial affects the productivity and this sector's competitiveness. decisions they have realized me on basis of a matter balance in the stages of the process, as on the stage of hair and the tanning stage and posteriorly in the treatment plant of residual waters, once was followed immediately of an evaluation of the economic costs, the profitability and the needs in the short run, where the criteria considerate are the following: Present Value Net ( VAN>0) : $7436.33; The ratio Benefit - Cost ( B/C>1): 1.07 and the values pullback Intern ( TIR>12%):16.39%. once was based in the fact-finding work's aftermaths, concludes the ecotechnologies proposed are fit to the effluent- liquids handling than them: Stripping the flesh from before the hair, Sieving with sieves in the process's zones, Re-use the hairnes's, Re-use's bathings the tanning bathings to the chrome, Installing sedimentation large puddles and finally Designing Treatment's Plant of Effluent Liquids in each tannery; Whereupon the contaminants unloadings it was been able to decrease in manner significant it discharge them of contaminants, in one 50 percent at clean treatment´s technologies and 95 percent at treatment technologie, improving environmental quality and promoting sustainable development.